Information System Design for Water Maintenance Activities at PT. Rezeki Surya Intimakmur - Derisfy, Fahmizal; Gebrina, Lusiana; Annisa, Syerlie (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
PT. Rezeki Surya Intimakmur is a company engaged in home and building maintenance. Currently PT. Rezeki Surya Intimakmur is currently under a work contract with PT. Chevron Pacific Indonesia (PT. CPI) in terms of clean water maintenance activities in the company environment and the housing for employees of PT. CPI. In managing clean water maintenance data every day, the company uses a manual method by recording, which is filling out a work assignment form. This method results in the management of clean water maintenance work being hampered because data on workers and work results are often inconsistent with the actual situation—applications designed using research and product development methods with the waterfall model. The application design process uses Visual Basic.Net programming language and MySQL database. The resulting can make it easier for admin staff to manage clean water maintenance activities to produce maintenance reports.